A dieta mediterrânica nos provérbios portugueses - Chacoto, Lucília (2014)
Title: «Mediterranean diet in Portuguese proverbs». Mediterranean diet has been considered Immaterial World Patrimony since December 2013. It is characteristic of basin Mediterranean people (Portugal, Spain, Morocco, Italy, Greece, Cyprus and Croatia) and includes their gastronomy with local products, their traditions, their culture and their healthy lifestyle. Mediterranean diet is passed on from one generation to another mostly orally and it is likewise present in phraseological units, especially in proverbs. This paper analyses Portuguese proverbs aiming to show their importance when transmitting cookingrelated knowledge and information, such as, local ingredients, cooking techniques and the social function, both daily or on holidays. Since the practice of physical exercise is so important for the Mediterranean diet, our study includes physical exercise and relaxation-related proverbs as well.